Nanocarbon Materials: Synthesis of Newly Discovered Carbon Nanoframes and Hollow Carbon Nanocubes - Zezhong Lin; Bingxuan Du; Conglin Zhang; Qingsong Ji; Xiaobo Yang; Haichao Li (Advanced Materials Interfaces)
Abstract Nanocarbons are emerging at the forefront of nanoscience, and a wide variety of nanocarbons with unique structures have appeared over the past two decades. Currently, many carbon nanostructures have not been synthesized in the field of nanocarbons. The focus of this work is to present a new ideology and report two carbon nanostructures that have never been reported before. Inspired by the phenomenon of crystal growth, a new concept of thought is proposed. In brief, the diversity of crystal structures is utilized to enable surfactants to replicate their framework structures to create carbon nanomaterials with novel structures. In this work, carbon nanoframes (CNFEs) and hollow carbon nanocubes (HCNBs) synthesized by the 3‐(N,N‐dimethyldodecylammonio) propanesulfonate (SB3‐12)@NaCl self‐assembly strategy are used as proof of the ideology concept. It is shown that the prepared CNFEs have tunable dimensions (320–565 nm) and specific optical properties (fluorescence). The obtained HCNBs are 575 ± 20 nm in size and have fluorescent properties. It is found that changes in the concentration of SB3‐12 are a key driver of size changes, especially morphological evolution. It is believed that the ideology of this work provides a new entry point for the synthesis of carbon nanomaterials.